2013
DOI: 10.1007/s12630-013-9929-3
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid use in the intensive care unit: a survey of intensivists

Abstract: Objective The efficacy of systemic corticosteroids in many critical illnesses remains uncertain. Our primary objective was to survey intensivists in North America about their perceived use of corticosteroids in clinical practice. Design Self-administered paper survey.Population Intensivists in academic hospitals with clinical trial expertise in critical illness. Measurements We generated questionnaire items in focus groups and refined them after assessments of clinical sensibility and test-retest reliability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…First, we developed explicit eligibility criteria based on the management of patients with ARDS and found that responses varied depending on disease severity and etiology: 12% of the respondents ac knowledged using corticosteroids "sometimes" or "most always" in ARDS, 22% "sometimes" or "most always" in severe ARDS, and 90% "some times" or "most always" in ARDS of unknown etiology. 22 A systematic review of community acquired pneumonia in hospitalized adults sug gests that corticosteroid treatment reduces mor tality, the need for mechanical ventilation, and length of hospital stay. 23 The guidelines pub lished by the Society of Critical Care Medicine and the European Society of Intensive Care Med icine suggest, with moderate certainty, using cor ticosteroids in patients with moderate to severe ARDS within 14 days of disease onset.…”
Section: Infectionsmentioning
confidence: 99%
“…First, we developed explicit eligibility criteria based on the management of patients with ARDS and found that responses varied depending on disease severity and etiology: 12% of the respondents ac knowledged using corticosteroids "sometimes" or "most always" in ARDS, 22% "sometimes" or "most always" in severe ARDS, and 90% "some times" or "most always" in ARDS of unknown etiology. 22 A systematic review of community acquired pneumonia in hospitalized adults sug gests that corticosteroid treatment reduces mor tality, the need for mechanical ventilation, and length of hospital stay. 23 The guidelines pub lished by the Society of Critical Care Medicine and the European Society of Intensive Care Med icine suggest, with moderate certainty, using cor ticosteroids in patients with moderate to severe ARDS within 14 days of disease onset.…”
Section: Infectionsmentioning
confidence: 99%
“…19,20 Although somewhat controversial, steroid supplementation has been thought to augment peripheral system hemodynamics and support some patients with acute adrenal insufficiency in the face of critical illness. 21 Interestingly, additional clinical trials testing the protective effects of corticosteroids after TBI did not demonstrate a therapeutic effect. The Corticosteroid Randomization after Significant Head Injury trial was a randomized, placebo-controlled multicenter trial designed to determine the effect of high-dose methylprednisolone in 10,008 patients with TBI across 239 hospitals in 49 countries.…”
Section: Introductionmentioning
confidence: 99%
“…Hormone lack secondary to viral pneumonia improve the curative effect of pulmonary fibrosis and the adverse effects of increased pulmonary infection, do not recommend hormones for the treatment of patients with influenza virus pneumonia [16][17][18]. This group of patients with paroxysmal cough violently, mechanical ventilation during the fight against severe, 2 cases of tension pneumothorax (50%).…”
Section: Discussionmentioning
confidence: 99%